Pembingkaian Pemberitaan Mengenai Omnibus Law (Ruu Cipta Kerja) Studi Framing Robert N. Entman Media Online detik.Com dan Tirto.Id - Hanafi, Hanafi; Sugiarta, Nugraha; Reza, Faisal; Ilham, Yanuar; Lestari, Anggita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The research entitled “News framing about the omnibus law (work copyright) study of framing Robert N. Entman in online media detik.com and tirto.id edition 6-10 October 2020” aims to find out how framing is done by detik.com and tirto. .id in reporting the Work Creation Bill or Omnibus Law. This research uses a qualitative method with a constructionist paradigm and uses the framing analysis approach of the Robert N. Entman model which consists of defining the problem, determining the cause of the problem (diagnosis cause), making moral decisions (make moral judgment), and recommending problem solving (treatment recommendation) on the news regarding the Omnibus Law (RUU Cipta Kerja) edition 6-10 October 2020. This research is focused on the subject matter, the author provides a limitation or research focus as well as research questions that will be the author's reference in conducting this research. The focus of this research is framing detik.com and tirto.id news regarding the ratification of the omnibus law edition 6-10 October 2020 based on the framing model of Robert N. Entman